Pendidikan Islam Menurut KH. Imam Zarkasyi - Zarkasyi, Muhammad Badruddin; Sarwanto, Sarwanto; Firdosi, Akh. Fad; Khoir, Mulyanto Abdullah; Halmianto, Halmianto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the thoughts and contributions of KH. Imam Zarkasyi in the renewal of Islamic boarding school education in Indonesia. The method used in this study is a literature review, with a case study approach. Data were obtained from books, journals, proceedings, magazines, and scientific articles, and analyzed using thematic analysis techniques that include the stages of comparison, contrast, and critique. The study's results indicate that the renewal of Islamic boarding school education was initiated by KH. Imam Zarkasyi is based on four main aspects, namely the renewal of the structure and management of Islamic boarding school institutions based on waqf, the development of an integrative curriculum that combines religious knowledge and general knowledge in a balanced manner, the implementation of a modern and organized classical boarding school education system and method, and the formation of the mindset of students through the internalization of the Panca Jiwa Pondok values. In addition, this study found that the concepts of the hidden curriculum and 24-hour education implemented at the Darussalam Gontor Modern Islamic Boarding School contributed significantly to the formation of students' characters as independent, broad-minded, and oriented towards social service. The educational thoughts of KH. Imam Zarkasyi is a relevant model for developing modern Islamic boarding schools that remain rooted in Islamic values and are adaptable to the demands of changing times.